ANALISIS EFEKTIFITAS ANGKUTAN UMUM SUMBAWA - EMPANG, EMPANG - SUMBAWA - Nursia; Kurniati, Eti; Hermansyah (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
Increased demand for transportation services to support community activitiesSumbawaEmpang or vice versa, the number of public transportation from time to time continuesincrease without any limitation on the number of fleets, so that the transportation performance does notis known. To overcome this, the number of public transportation needs to be adjusted to theavailable passenger needs by analyzing the performance of public transport.The purpose of this study is to determine the effectiveness of public transport performance inthe Sumbawa Empang route and vice versa. The method used by doingapproach based on the Director General of Land Transportation NoSK.687/AJ.206/DRJD/2002 concerning the operational performance of public transport. Research resultThe load factor values ??obtained are 87.4% and 89.7% in the category of transportation performancequite good, the average frequency is 2 vehicles/hour, the average headway is 26 minutes and 23 minutes,service time is 9.30 hours and 8.30 hours in the category of poor transportation performance, andaverage speed 27.12 km/hour and 38.52 km/hour, travel time 4.05 hours and 2.57hours, the average waiting time is 13 minutes and 12 minutes in the category of good transportation performance.The results of data analysis show that the performance of Sumbawa Empang public transportation,There are four parameters of the Sumbawa Empang that do not reach the effective category that isdoes not meet and exceeds the standard, so there needs to be improvements from the Departmentcommunication.